A model to evaluate the effect of shading objects on the energy yield gain of bifacial modules. (February 2019) - Zhu, Qiangzhong; Zhu, Chen; Liu, Songmin; Shen, Chanjun; Zhao, Wei; Chen, Zhenbo; Chen, Ling; Wang, Jianbo; Wang, Lichun; Zhang, Shengcheng; Lv, Jun
Highlights: Developed an optical mode to evaluate the shading effect of the system holders and frames. A 40 mm square beam could introduce 49% optical loss to the bifacial modules without system design optimizing. The irradiation loss by frame could be 6–18%, which depends on the frame height. The shading objects should be smaller and 40 mm far away from the modules to get high energy yield gain of bifacial modules. Abstract: Bifacial modules become popular due to the backside yield gain, which can reduce the levelized cost of energy (LCOE) of photovoltaic system dramatically; the technical development of bifacial cell and double glass module technology are also important for the explosion of bifacial market. More and more people are attracted by the energy yield gain of bifacial modules; however, only little studies focus on the effect of backside shading objects on the module and system that would influence the energy yield gain. In this paper, an optic model is developed to evaluate the effect of the shading objects. The energy loss by the shading objects is also estimated by simulation and experiment. The result shows that when the shading objects are 40 mm vertical away from the modules, the shading effect could be greatly reduced. The frame height of bifacial modules should be smaller to reduce the shading effect by frames. It is better to remove the surface C of the frames to optimize the energy yield ability of bifacial modules.